Hunting and wildlife use in protected areas of the Atlantic rainforest, northeastern Brazil - Barbosa, José Aécio Alves; Aguiar, José Otávio; Alves, Rômulo Romeu da Nóbrega (Desenvolvimento e Meio Ambiente, 2022)
Despite being considered illegal in Brazil, the hunting of wild animals is a very common practice that influences the conservation of several fauna species. As such, the knowledge and practices associated with hunting activities need to be researched. Thus, the present study aimed to investigate, from an ethnozoological approach, the capture, slaughter and use of wild animals in four Conservation Units (protected areas) in the Atlantic Rainforest in the state of Paraíba. 109 hunters were interviewed, and 156 game animals were registered, which were distributed across the categories: mammals (31), birds (93), reptiles (27) and amphibians (05). The use of wild fauna registered in this study is mainly associated with the consumption of meat; however, the use of animals aspets, trade, zootherapy and control hunting were also recorded. Hunting practices have existed for a long time in the study region and are currently, mainly, motivated by subsistence, excluding occurrences of hunters killing animals that they considered to be dangerous. The socioeconomic situation of hunters and their possible dissonance with the laws that regulate wildlife protection are fundamental aspects that contribute to a better understanding of the barriers and possible methods of wildlife conservative management in the region. The catalog of hunted game animals expands our knowledge about the fauna hunted in the state of Paraíba, where research has not yet been performed on hunting activities in Conservation Units (protected areas) in the Atlantic Rainforest, this being the first evaluation. We hope that our results will contribute to the implementation / improvement of public policies aimed at the management of local wildlife, which endeavor to conserve the region's biodiversity.